Professional-public interaction In the post-war reconstruction of beirut. Theoretical approaches And dissemination of relevant practices (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The complex story of Beirut's reconstruction after a 15-year civil war is seen as aparadigm for post-war Ukraine. In the recovery of the capital of Lebanon, collaboration between thepublic and professional sectors played an important role, acting as an alternative or complement tostate and commercial private strategies. In contrast to «Solidere» company commercial approach,marked by "architectural amnesia" and the destruction of historical heritage, both publicorganizations and professional communities of architects and historians advocate for thepreservation of cultural heritage as the basis for national reconciliation.The emergence of public movements from the level of direct self-organization of thepopulation was complicated by the specifics of Lebanese society - the stability of ethnoconfessionalidentity and the corresponding political mobilization after the civil war. The dynamicsof interaction allow traditional elites to penetrate civil society and connect the possibilities of itsconstructive participation in the reconstruction of the city.The dominant "top-down" approaches were focused on the physical aspects of reconstruction,and alternative approaches have also gained some development. However, they were conducted insmall settlements, because creating a holistic methodology for Beirut was beyond the currentcapabilities of progressive research teams, and breakthroughs towards an effective humanitarianapproach to post-war reconstruction came too late.
Keywords: post-war urban reconstruction; urban development; professional-public interaction; public participation; third sector; cultural heritage; Arab world; thnic-confessional stratification; archaeology